Avibactam Sensitizes Carbapenem-Resistant NDM-1–Producing Klebsiella pneumoniae to Innate Immune Clearance - Ulloa, Erlinda R (J Infect Dis, 2019)
Infections caused by New Delhi metallo-β-lactamase (NDM)–producing strains of multidrug-resistant Klebsiella pneumoniae are a global public health threat lacking reliable therapies. NDM is impervious to all existing β-lactamase inhibitor (BLI) drugs, including the non–β-lactam BLI avibactam (AVI). Though lacking direct activity against NDMs, AVI can interact with penicillin-binding protein 2 in a manner that may influence cell wall dynamics. We found that exposure of NDM-1–producing K. pneumoniae to AVI led to striking bactericidal interactions with human cathelicidin antimicrobial peptide LL-37, a frontline component of host innate immunity. Moreover, AVI markedly sensitized NDM-1–producing K. pneumoniae to killing by freshly isolated human neutrophils, platelets, and serum when complement was active. Finally, AVI monotherapy reduced lung counts of NDM-1–producing K. pneumoniae in a murine pulmonary challenge model. AVI sensitizes NDM-1–producing K. pneumoniae to innate immune clearance in ways that are not appreciated by standard antibiotic testing and that merit further study.